2021
DOI: 10.33545/26164485.2021.v5.i1e.322
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tract infection and homoeopathy

Abstract: Urinary tract infection is the most common disorder of the renal tract. Although serious morbidities from UTI are very low but if left untreated that can lead to serious complications. Bacteraemia from UTI can be a life-threatening medical emergency. Homoeopathy is a holistic medical practice that treats the patient as a whole. Homoeopathic medicines are a useful alternative to conventional medication offering earlier symptom resolution, cost effectiveness and fewer adverse Urinary tract infection and their co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This study was concluded by Desarada K et.al by mentioning some homoeopathic medicines such as cantharis, Nux vomica, sarsaparilla, Apis Mellifica, Staphysagria, nitric acid and Terebinthina for treating urinary tract infection. (22) Likewise, integrated management of antibiotic-resistant Urinary tract infection (2020) by Kusum studies 2 cases of UTI where the Naranjo criteria total score in the study for each case was found like +10/13 and +9/13 respectively which concluded that addition of homoeopathy to the integrated management of antibiotic resistance urinary tract infection is effective approach. (23) CONCLUSION Urinary tract infection (UTI) is a very common clinical condition among the women specially in adolescent girls' reason could be many including frequent usage of common washrooms, improper usage of menstrual pads, excessive sexual activity, and lack of personal hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…This study was concluded by Desarada K et.al by mentioning some homoeopathic medicines such as cantharis, Nux vomica, sarsaparilla, Apis Mellifica, Staphysagria, nitric acid and Terebinthina for treating urinary tract infection. (22) Likewise, integrated management of antibiotic-resistant Urinary tract infection (2020) by Kusum studies 2 cases of UTI where the Naranjo criteria total score in the study for each case was found like +10/13 and +9/13 respectively which concluded that addition of homoeopathy to the integrated management of antibiotic resistance urinary tract infection is effective approach. (23) CONCLUSION Urinary tract infection (UTI) is a very common clinical condition among the women specially in adolescent girls' reason could be many including frequent usage of common washrooms, improper usage of menstrual pads, excessive sexual activity, and lack of personal hygiene.…”
Section: Discussionmentioning
confidence: 99%